Origin, Stemness, Marker and Signaling Pathway of Oral Cancer Stem Cell - Dicha Yuliadewi Rahmawati; Hernindya Dwifulqi; Ferry Sandra (Cell and BioPharmaceutical Institute, 2020)
Cancer constitutes of complex heterogeneous organ-like structures with a hierarchical cell structure, and only minor phenotypic subpopulations with stem-like properties have a dual capacity to indefinitely self-renew and generate all heterogeneous cell phenotypes consisting of bulk tumor cells. Cancer stem cells (CSC) has similar properties to ordinary stem cells. It is understood that CSC is responsible for the recurrence of metastasis and drug resistance. Thus, control of CSC can provide successful therapy intervention that inhibits cancer growth and aggressive behavior. Conventional cancer therapy is realized to be insufficient for oral cancer therapy. Meanwhile, accurate targeting of OCSC has proved to be a significant challenge due to the commonality of many markers between OCSC and healthy cells. This article discusses the current understanding of oral CSC, with focus on origin, stemness, marker and signalling pathway.Keywords: oral cancer stem cell, CSC, marker, origin, stemness, therapy